Methicillin‐resistant Staphylococcus aureus screening as a patient safety initiative: using patients' experiences to improve the quality of screening practices. Issue 1 (21st September 2013) - Currie, Kay; Knussen, Christina; Price, Lesley; Reilly, Jacqui
<x xml:space="preserve">Abstract</x> Aims and objectives To explore the patient experience and acceptability of methicillin‐resistant Staphylococcus aureus screening of inpatient admissions to acute hospital settings. Background Prevention of healthcare‐associated infections such as methicillin‐resistant Staphylococcus aureus is a major patient safety concern internationally. Screening of patients for methicillin‐resistant Staphylococcus aureus colonisation is becoming a routine aspect of hospital admission; however, evidence of the patient experience and acceptability of methicillin‐resistant Staphylococcus aureus screening is limited. Design A mixed‐methods study set in six acute care hospitals in three Scottish regions. Methods Data collection involved postdischarge self‐report survey of patients who had been screened (n = 54) and qualitative patient interviews (n = 10). Theoretical constructs derived from the Health Belief Model and Theory of Planned Behaviour used in analysis. Results Findings indicated that methicillin‐resistant Staphylococcus aureus screening was broadly acceptable to patients. The experience of screening did not appear to be problematic; responses demonstrate that screening provided reassurance and generated confidence that health organisations were tackling healthcare‐associated infections. Patients were less positive regarding the provision of information, the possibility of refusing a screen and the consequences of a positive test result. Furthermore, there were indications that patients wanted to be told the results of the screen and strong support for screening of hospital staff. Conclusions Analysis of constructs from our theoretical frameworks provides evidence that attitudes were largely positive; responses indicate a belief in the beneficial impact of methicillin‐resistant Staphylococcus aureus screening for patients and the wider community. However, it is important that health professionals continually assess the patient experience of 'routine' aspects of health care such as MRSA screening. Relevance to clinical practice The findings from this study suggest that while methicillin‐resistant Staphylococcus aureus screening is generally acceptable to patients as a regular patient safety initiative, to enhance the quality of the patient experience, clinicians should consider the timing, content and effectiveness of information provision.